Effects of No-tillage of Rice on Blue and Green Water at Basin Scale - LUO Kaisheng (Renmin Zhujiang)
It is of great significance to study the hydrological effect of no-tillage of rice for the popularization of no-tillage technology and the sustainable development of agriculture.However,previous studies were mainly conducted at station scale,and the effect of no-tillage of rice on blue-green water at basin scale is still unclear.Taking the Xiangjiang River Basin as the test area,based on the land use data,digital elevation data,soil data,agricultural management data in 2000 and meteorological data-driven SWAT model,this paper simulates the effect of no-tillage of rice on blue water (water yield+deep groundwater recharge) and green water (actual evapotranspiration+soil moisture content) in the basin.The results show that:Compared with traditional tillage,no-tillage of rice had a greater influence on recharge of deep groundwater,resulting in a decrease of 5.62%,which was 5.35% higher than that of water yield.However,the change of blue water was mainly attributed to the change of water yield,whose contribution was 72.46%.The green water flow (actual evapotranspiration) decreased by 8.460×107 m3 due to no-tillage of rice,but the increase of green water reservoir (soil moisture content) offset these and eventually resulted in the increase of green water.Therefore,the change of blue-green water distribution under no-tillage of rice was mainly achieved by changing water yield and soil moisture content.The water yield mainly caused the change of blue water,while the soil moisture content mainly resulted in the change of green water.Due to the mutual offset of hydrological factors,there was no significant final effect of no-tillage rice on the blue-green water of the whole basin,but large spatial differences within the basin.No-tillage of rice increased the proportion of green water in the total water resources,and increased the ecological water available in the farmland ecosystem,so it played a positive role.